Reduced visual cortex grey matter volume in children and adolescents with reactive attachment disorder - Shimada, Koji (Neuroimage Clin, 2015)
Child maltreatment increases the risk for psychiatric disorders throughout childhood and into adulthood. One negative outcome of child maltreatment can be a disorder of emotional functioning, reactive attachment disorder (RAD), where the child displays wary, watchful, and emotionally withdrawn behaviours. Despite its clinical importance, little is known about the potential neurobiological consequences of RAD. The aim of this study was to elucidate whether RAD was associated with alterations in grey matter volume (GMV). High-resolution magnetic resonance imaging datasets were obtained for children and adolescents with RAD (n = 21; mean age = 12.76 years) and typically developing (TD) control subjects (n = 22; mean age = 12.95 years). Using a whole-brain voxel-based morphometry approach, structural images were analysed controlling for age, gender, full scale intelligence quotient, and total brain volume. The GMV was significantly reduced by 20.6% in the left primary visual cortex (Brodmann area 17) of the RAD group compared to the TD group (p = .038, family-wise error-corrected cluster level). This GMV reduction was related to an internalising problem measure of the Strength and Difficulties Questionnaire. The visual cortex has been viewed as part of the neurocircuit regulating the stress response to emotional visual images. Combined with previous studies of adults with childhood maltreatment, early adverse experience (e.g. sensory deprivation) may affect the development of the primary visual system, reflecting in the size of the visual cortex in children and adolescents with RAD. These visual cortex GMV abnormalities may also be associated with the visual emotion regulation impairments of RAD, leading to an increased risk for later psychopathology.